Computational modeling of cardiac optogenetics: Methodology overview & review of findings from simulations. (1st October 2015) - Boyle, Patrick M.; Karathanos, Thomas V.; Entcheva, Emilia; Trayanova, Natalia A.
Abstract: Cardiac optogenetics is emerging as an exciting new potential avenue to enable spatiotemporally precise control of excitable cells and tissue in the heart with low-energy optical stimuli. This approach involves the expression of exogenous light-sensitive proteins (opsins) in target heart tissue via viral gene or cell delivery. Preliminary experiments in optogenetically-modified cells, tissue, and organisms have made great strides towards demonstrating the feasibility of basic applications, including the use of light stimuli to pace or disrupt reentrant activity. However, it remains unknown whether techniques based on this intriguing technology could be scaled up and used in humans for novel clinical applications, such as pain-free optical defibrillation or dynamic modulation of action potential shape. A key step towards answering such questions is to explore potential optogenetics-based therapies using sophisticated computer simulation tools capable of realistically representing opsin delivery and light stimulation in biophysically detailed, patient-specific models of the human heart. This review provides (1) a detailed overview of the methodological developments necessary to represent optogenetics-based solutions in existing virtual heart platforms and (2) a survey of findings that have been derived from such simulations and a critical assessment of their significance with respect to the progress of the field. Graphical abstract: Highlights: In Part 1, we discuss state-of-the-art methods used to model cardiac optogenetics. Required techniques at the protein, cell, tissue, and organ scales are summarized. A novel exploration of optogenetic cardiac action potential silencing is included. In Part 2, we review findings that have emerged from cardiac optogenetics modeling. Simulations will help assess the efficacy of potential clinical applications.